Nonhuman Agencies in the Twenty-First-Century Anglophone Novel
XVII, 320 p. 3 illus.
Keywords: This book offers an overview on the growing field of nonhuman studies in relation to Anglophone novels. It illuminates the variety of nonhuman actors that take centre stage in the twenty-first-century novel and the formal changes that the Anthropocene, the digital turn, the animal rights movement, and research into plant consciousness have brought to the novel as a form. The book is divided into four sections, each focusing on a different aspect of twenty-first-century literature that engages with the nonhuman. The collection investigates how the environmental changes and the increasing use of AI technologies have fostered the flourishing of genres like the New Weird, Climate Fiction, and speculative fiction, how it makes us embrace new perceptions of life in relation to genetic engineering, and how it forces us to engage with newly emerging political contexts. Yvonne Liebermann is Lecturer and Research Assistant at Heinrich-Heine-University Duesseldorf, Germany. She is currently completing a book Latency and Memory in Contemporary Anglophone Literature. She has written articles in the field of contemporary literature, which have been published in peer-reviewed journals including European Journal of English Studies and Ariel: A Review of International English Literature, together with Birgit Neumann. Judith Rahn is Lecturer in the Department of English and American Studies at Heinrich-Heine-University Duesseldorf, Germany. She is currently finishing her book Exploring Posthuman Life in Contemporary Fiction and is co-editor of the special issue Afrofuturism’s Transcultural Trajectories (2020, with Eva U. Pirker). She is author of (Re-)Negotiating Black Posthumanism – The Precarity of Race in Nnedi Okorafor's Lagoon (2019). Bettina Burger is Lecturer in Postcolonial and Anglophone Literatures at the University of Duesseldorf, Germany. She has previously organised a successful conference on the topic of Nonhuman Agency in Anglophone Literatures. Her publications include contributions to the Literary Encyclopedia and an article on challenges to Western science in Nnedi Okorafor’s Africanfuturist fiction. .